(untitled) (Estudos em Design, 2015)
We present recommendations for the design of technical drawings systems development, resulting from studies on the use of clipboards for design by the students of IFBA. For this, he was elected as a methodological strategy Ergonomizadora intervention. In Ergonomic Assessment showed that the concentration in performing the tasks is impaired by physical discomfort felt by users, evidenced in interviews and photographic records. The systematization of SHTM (Human Task-Machine System) presented the problems through tables and flowcharts. In Ergonomic Diagnose characterized the problems of interfacial order detected. Task analysis and questionnaires and rating scales were performed.